Insights into structural and magnetic properties of manganite perovskite La0.7Ca0.3Mn0.6Co0.4O3 nanoparticles prepared by sol gel auto combustion route - R. Sharma; P. Kumar; Anil (Physics Open)
The calcium and cobalt co-doped Lanthanum Manganite (La0.7Ca0.3Mn0.6Co0.4O3) polycrystalline ceramic was synthesized by sol-gel autocombustion route. The codoping strategy was adopted to study the synergistic effect of incorporating both Ca2+ and Mn3+ ions in the structural and magnetic properties of LaMnO3 perovskite for technical applications. The as-prepared sample was characterized by XRD, SEM, FTIR and VSM. XRD study confirmed the formation of a single phase compound with an orthorhombic crystal structure having Pbnm space group. The lattice parameters obtained by reitveld refinements are: a = 5.4406 Å, b = 5.4921 Å and c = 7.7159 Å. The crystallite size was calculated from scherrer method, williamson hall plot, modified scherrer plot, size strain plot, halder wagner plot, reitveld method and compared. The diverse morphology was confirmed by FESEM analysis, while FTIR spectra shows presence of MnO6 octahedra. Magnetic studies through VSM confirms antiferromagnetic behavior and moderate values of saturation magnetization and coercivity along with higher magnetocrystalline anisotropy, thus suggesting potential application in the field of magnetic sensors like AMR sensors and read heads of hard disk in magnetic data storage applications.